Perlindungan Hukum Bagi Pemegang Hak Merek Superman Terhadap Pelanggaran Merek - Syafira, Viona Talitha (Jurnal Suara Hukum, 2021)
Owners of well-known marks in Indonesia have in some cases been rejected when submitting their application for registration by DGIP because most of the similar marks have already been registered. For example, PT. Marxing Fam Makmur by registering the Superman trademark while it was registered first by DC Comics. So, the problem is how the protection of Superman's trademark rights holders based on Law No. 20 of 2016, and how is the decision of the Commercial Court judge in ruling on trademark disputes. This study uses normative research methods which are sourced from secondary data as a support for qualitative analysis. Based on the analysis, it is known that the Superman brand belongs to PT. Marxing Fam Makmur has similarities in essence to the Superman brand owned by DC Comics and the Superman trademark registrant has bad intentions, so DC Comics as the owner of the Superman mark has the right to file a trademark cancellation lawsuit to the Central Jakarta Commercial Court. In the lawsuit, DC Comics did not prepare the lawsuit accurately and clearly so that the lawsuit became vague and the judge decided that the lawsuit was declared unacceptable